2018
DOI: 10.1186/s12889-018-5757-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of perinatal mortality among cohorts of pregnant women in three districts of North Showa zone, Oromia Region, Ethiopia: Community based nested case control study

Abstract: BackgroundStatistics indicate that Ethiopia has made remarkable progress in reducing child mortality. It is however estimated that there is high rate of perinatal mortality although there is scarcity of data due to a lack of vital registration in the country. This study was conducted with the purpose of assessing the determinants and causes of perinatal mortality among babies born from cohorts of pregnant women in three selected districts of North Showa Zone, Oromia Region, Ethiopia. The study used community b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 24 publications
9
42
2
2
Order By: Relevance
“…Prematurity was one of the strongest determinants of perinatal mortality in this study. The odds of experiencing perinatal mortality were 3.29 fold more likely among premature births compared to those mature births (AOR 3.29, 95%CI;1.86-5.81).This finding was in line with the studies conducted in Gojjam(6),Tigray(16), Oromia (17),Tanzania (18),Zimbabwe(13),Ghana (19) and Kerala, India (20).The study also conducted in Haryana, India (21) showed that odds of perinatal mortality in premature deliveries were about 3.5 times more likely when compared to term deliveries. The other case control study conducted in Brazil(22) also indicated that prematurity was associated with perinatal mortality.…”
Section: Discussionsupporting
confidence: 86%
“…Prematurity was one of the strongest determinants of perinatal mortality in this study. The odds of experiencing perinatal mortality were 3.29 fold more likely among premature births compared to those mature births (AOR 3.29, 95%CI;1.86-5.81).This finding was in line with the studies conducted in Gojjam(6),Tigray(16), Oromia (17),Tanzania (18),Zimbabwe(13),Ghana (19) and Kerala, India (20).The study also conducted in Haryana, India (21) showed that odds of perinatal mortality in premature deliveries were about 3.5 times more likely when compared to term deliveries. The other case control study conducted in Brazil(22) also indicated that prematurity was associated with perinatal mortality.…”
Section: Discussionsupporting
confidence: 86%
“…A total of 35 studies included in this review. However, studies included in the meta-analysis were thirty four [ 1 3 , 8 , 11 , 12 , 18 – 45 ]. Pregnant women, women attending for labor and delivery service and newborns were study participants considered for data source in primary studies.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to this, studies identified multiple risk factors for perinatal mortality such as prematurity, low birth weight, previous history of perinatal death, not receiving tetanus toxoid immunization, lack of Iron supplementation etc. [ 1 , 3 , 11 , 12 ]. On the other side, closely spaced pregnancies are hypothesized as one of the risk factors for poor perinatal outcomes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perinatal mortality in our study was found to be highest in the age group of 30-35 years (p-value 0.02) despite lesser number of deliveries (than 25-30 years). A recently published nested case control study done Elias Merdassa Roro et al supports the study's observation, viz mothers aged 35 years and above had a higher risk of losing their newborn 10 babies to perinatal deaths than younger mothers. Preterm births had a higher risk of perinatal death than term babies.…”
Section: Discussionmentioning
confidence: 73%